Perahu Layar Sebagai Inspirasi Penciptaan Karya Seni Lukis Kubisme - Rajagukguk, Kevin Gerald; Supriyatini, Sri; Tjokropramono, I Gede Yosef (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
MBKM Independent Project Report carries the title “Sailboats as Inspiration for the creation of Cubism Painting Works. It started with the author making works using cubism techniques and seeing the shape of sailboats as suitable for combining these techniques to create works of art. The problem that is obtained is how to visualize sailboats in each work in visualizing, the author uses methods and techniques obtained from the MBKM process, the goals and benefits and develops the creativity of the author in expressing imaginary forms and images/photos that are edited accordingly the needs of the author in the process of creating. The author is also assisted by I made Gunawan as an artist who guides the creation of works and uses a creation method which includes several stages of contemplation, basic research, exploration, experimentation, execution, completion. From this process the author produces works entitled 1) "Berlash", 2) "Boats and the moon", 3. "Equipment", 4) "Reliable Sailers", 5) "Stranded", and 6) "Remembrance" It can be concluded that the author created the work because of his interest in embossed leaves, with ideas originating from phenomena captured at the Kaki Bisma Batan Timbul studio and reading reference sources from the internet. At the processing stage, the writer combines the techniques from the MBKM results and the techniques that the writer gets on campus, to be realized in 2-dimensional From all these processes it is hoped that one can find identity in work.